2009
DOI: 10.1007/s10508-008-9449-3
|View full text |Cite
|
Sign up to set email alerts
|

Does Physical Abuse, Sexual Abuse, or Neglect in Childhood Increase the Likelihood of Same-sex Sexual Relationships and Cohabitation? A Prospective 30-year Follow-up

Abstract: Existing cross-sectional research suggests associations between physical and sexual abuse in childhood and same-sex sexual orientation in adulthood. This study prospectively examined whether abuse and/or neglect in childhood were associated with increased likelihood of same-sex partnerships in adulthood. The sample included physically abused (N = 85), sexually abused (N = 72), and neglected (N = 429) children (ages 0-11) with documented cases during 1967-1971 who were matched with non-maltreated children (N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(38 citation statements)
references
References 52 publications
0
36
0
2
Order By: Relevance
“…Sexual minorities have been reported to have a 1.6 to 3.9 times higher risk of PTSD compared to a heterosexual reference group [41]. Several studies have found elevated prevalence of both childhood maltreatment and adulthood PTSD in sexual orientation minorities [42,43].…”
Section: Sexual Orientationmentioning
confidence: 99%
“…Sexual minorities have been reported to have a 1.6 to 3.9 times higher risk of PTSD compared to a heterosexual reference group [41]. Several studies have found elevated prevalence of both childhood maltreatment and adulthood PTSD in sexual orientation minorities [42,43].…”
Section: Sexual Orientationmentioning
confidence: 99%
“…Najman et al [88] ermittelten in einer großen populationsbasierten studie Zusammenhänge zwischen Missbrauchserfahrungen und verschiedenen sexuellen Funktionsproblemen (im hinblick auf sexuelles interesse, erregung, Orgasmus, schmerzen beim Geschlechtsverkehr). Weitere Merkmale, die mit Missbrauchserfahrungen in Verbindung gebracht werden, sind homosexuelle beziehungen bei Männern [150], hyperund hyposexualität [112] sowie spezifische sexuelle Selbstschematamerkmale bei missbrauchten Frauen, die sich u. a. als weniger verantwortlich und moralisch, weniger leidenschaftlich und romantisch charakterisieren [91]. Noll et al [96] berichten ablehnende und ambivalente haltungen zu sexualität, die in der Gruppe der vom biologischen Vater missbrauchten Frauen stärker waren als bei anderen täter-Opfer-Konstellationen.…”
Section: Sexualitätunclassified
“…Lesbians were victimized at rates of 15.6% to 85%, compared to 11% to 17% of heterosexual women (Rothman, Exner, & Baughman, 2011;Todahl, Linville, Wheeler, & Gau, 2009;Wilson & Spatz Widom, 2010). However, critiques of this research have argued that most of these studies did not discern between same sex victimization and heterosexual victimization, thus making the findings unclear if the perpetrator was the same sex as the victim or not (Waldner-Haugrud & Vaden Gratch, 1997).…”
Section: Sexual Minorities and Victimizationmentioning
confidence: 79%